Aerodynamics and cycling - Martin, J.
It is very popular to use the term `aero` to describe bicycles, wheels, helmets, and handlebars. However, do we really know exactly what `aero` means, and what the consequences of aerodynamics are to you, hich we measured drag in the wind tunnel of seven riders, then had them ride at three steady state velocities while we measured power with an SRM crank and wind conditions with an anamometer.The results indicate that our predicted power matched our measured power with a standard error of 5 watts, and demonstrate that this isa valid model for power during real world cycling.